Potential Value of Circular RNA circTBC1D4 in Gastrointestinal Stromal Tumors - null Chunyan-Zou; null Yanpeng-He; null Changshun-Xie; null Fulai-Gao; null Xiaoli-Xie; null Xiukun-Chai; null Chenxi-He; null Dongqiang-Zhao (Journal of Immunology Research)
Aims. To explore the expression of circular RNA (circRNA) in gastrointestinal stromal tumors. Background. Gastrointestinal stromal tumors (GIST) are mainly distributed in the stomach and small intestine. Recently, it has been verified that circular RNA (circRNA) has an important function in the regulation of GIST. Nevertheless, detailed investigations of circRNA-miRNA-mRNA regulatory networks in GIST are lacking. Objective. To analyze the gastrointestinal stromal tumor circRNA-miRNA-mRNA network, assessing the effect of circle RNA in gastrointestinal stromal tumors. Method. All the differential circRNAs and mRNAs were obtained from Gene Expression Omnibus (GEO) microarray data (GSE131481 and GSE147303, GSE131481, and GSE13861). Furthermore, a circRNA-miRNA-mRNA network was established. Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment were used to reveal the correlation between the functions of signaling pathways and target genes. The hub genes of protein-protein interaction (PPI) network and cytoHubba were also defined. Quantitative real-time PCR (qRT-PCR) was used to measure the expression levels of hsa-circ-0002917 (circTBC1D4), hsa-miR-590-5p (miR-590-5p), and PLN. Results. PPI network and Cytoscape showed that ATP1A2, PLN, KCNMA1, and SCNN1B were four central DEGs. GO analysis results revealed that DEGs were involved in negative management of myocardial contraction, regulation of myocardial cell contraction, ethanol oxidation, cellular potassium ion homeostasis, and relaxation of cardiac muscle, and KEGG analysis showed that major DEGs were with cGMP-PKG signaling pathway. Moreover, we obtained two pairs of axes, namely, hsa-circ-0039216/hsa-miR-338-3p/ATP1A2 and hsa-circ-0002917/hsa-miR-590-5p/PLN. The target of TBC1D4 is miR-590-5p, and miR-590-5p increased after knocking down TBC1D4. Moreover, PLN was the target of miR-590-5p, and miR-590-5p exerts antitumor effects by reducing PLN. Conclusions. In this study, we constructed a circRNA-miRNA-mRNA management network interrelated with GIST and researched the potential roles of circRNA. Moreover, we discovered a new molecular landmarker for the prediction, diagnosis, and therapy of patients.